Effect of sublethal Concentration of phenyl mercuric Acetate on respiratory metabolism of Tilapia Mossambica, peters and Its Recovery - Rama Chandra Bisoyi,; Nirmal Chandra Biswal,; Devi Prasad Samanta, (The Bioscan, 2025)
The effect of a sublethal concentration of phenyl mercuric acetate (0.06 mg/L) on the whole body oxygen uptake, ventilation rate & tissue slice respiration of laboratory acclimatized freshwater fish, Tilapia Mossambica, peters was studied with the increase in exposure period the ventilation rate showed a significant declining trend. The whole animal oxygen uptake decreased significantly with the increase in exposure period. A maximum of 83.5% inhibition was observed on 28 d of exposure. The tissue slice respiration showed a declining trend in vivo with the increase in exposure period. Brain slice respiration declined significantly with the increase in exposure period. Exposed liver slices and muscle slices also behaved identifically. However, the effects were more pronounced at early periods of exposure in case of liver & muscle. Gill slice respiration showed significant variation and was much more pronounced then the other tissues. It showed highest inhibition indicating highest damage caused to the tissue by PMA in exposed fish, when compared to liver, muscle and brain of exposed fish. In in vivo studies, with the increase in PMA concentration the oxygen uptake reduced drastically and maximum reduction was observed at 0.5 mg/L. of PMA. When the exposed fishes were transferred to PMA free medium, partial recovery was observed in ventilation rate, whole animal uptake rate, liver slice respiration and gill slice respiration. No recovery was marked in brain slice respiration. In addition, further depletion was marked in recovery period. A positive significant recovery was marked in case of muscle tissues of the exposed fishes, in recovery medium.